2013
DOI: 10.1007/s00592-013-0469-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA genetic variations: association with type 2 diabetes

Abstract: MicroRNAs are small single-stranded molecules that have emerged as important genomic regulators in different pathways. Different studies have shown that they are implicated in the metabolism and glucose homeostasis, and therefore, they could also be involved in the pathogenesis of metabolic disorders such as type 2 diabetes (T2DM). The aim of this study was to verify whether genetic variations in candidate microRNA (miRNA or miR) genes could contribute to T2DM susceptibility. We have selected 13 miRNAs as cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 22 publications
4
74
1
1
Order By: Relevance
“…Emerging evidence shows that single nucleotide polymorphisms (SNPs) within miRNA genes or miRNA-binding sites can alter the binding affinity of miRNAs to target mRNAs and thus influence target gene expression [7]. These kinds of SNPs are known to contribute to susceptibility to a variety of diseases, including cancer, cardiovascular disease, osteoporosis, and T2DM [8][9][10][11]. However, no studies to date have attempted to identify SNPs in miRNA-binding sites (miR-bindingSNPs) that associate with GDM risk.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence shows that single nucleotide polymorphisms (SNPs) within miRNA genes or miRNA-binding sites can alter the binding affinity of miRNAs to target mRNAs and thus influence target gene expression [7]. These kinds of SNPs are known to contribute to susceptibility to a variety of diseases, including cancer, cardiovascular disease, osteoporosis, and T2DM [8][9][10][11]. However, no studies to date have attempted to identify SNPs in miRNA-binding sites (miR-bindingSNPs) that associate with GDM risk.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are associated with different biological processes, including cell proliferation, differentiation and apoptosis [12]. It has been reported that aberrant miRNA expression is associated with the pathogenesis of type 2 diabetes [13, 14]. For example, miR-375 could regulate insulin secretion [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that genotype distributions were significantly different between groups (p < 0.05) and that the rs895819-C allele is more frequent in controls (p = 0.030, OR = 0.72, 95 % CI 0.53-0.97). association studies (GWAS) recently suggested that also genetic variations in noncoding regions could give a contribution to the disease phenotype [1,4]. MicroRNAs (miRNAs), a new family of small noncoding RNAs, have demonstrated to play substantial roles in many pathophysiological processes [5].…”
Section: Introductionmentioning
confidence: 99%